Coping with prospective memory failures : an effective reminder system design - Hou, Jinghua (2019)
The thesis work dealt with prospective memory failures especially for elderly. It proposed a comprehensive computational model for producing an effective reminding plan to remind people with an optimal number of reminders, and remind people at the right time with the right method. It also conducted in-depth experiments to evaluate the effectiveness of the proposed reminding plan.